Latar Omah Art – Desa Wisata Kaki Langit: Integrasi Kerajinan “Lukis Api” dan Homestay “Sahara” Menuju Wisata Berkelanjutan - Tanto Lailam; Awang Darumurti; Ani Yunita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This service program focuses on developing competitive and cultured superior village tourism, with the leading partner as the latar omah art of kaki langit village tourism. This service is carried out with an empowerment approach (active participation) through training, mentoring, and facilitation. Some of the programs carried out are (1) training and practice of painting fire for the community of mangunan and surrounding areas, which aim to support the fire painting program and improve human resources in the field of crafts; (2) excellent service training for culinary and homestay managers, homestay managers are expected to have practical, friendly, professional homestay management; (3) facilitation of fire painting tools as a medium for innovating craft tourism; (4) tourism packaging and promotion as a means to introduce and develop tourism villages in a sustainable manner.